Reading climate: subject English beyond the colonial. - Archer-Lean, Clare; Phillips, Sandra R.; Truman, Sarah E.; McLean Davies, Larissa (Discourse: Studies in the Cultural Politics of Education, 2025)
This paper outlines the emergent findings and theoretical foundations of Reading Climate: Indigenous literatures, English and Sustainable Futures, cross disciplinary research in Indigenous Studies, Education, and Literary Studies. Our team investigates epistemologies for the teaching of secondary subject English and tertiary courses and how they might be productively reworked. We draw on 'Indigenous relationality' as proposed by Mary Graham, Elder Scholar of the Kombumerri clan of the Yugambeh Nation as a core principle in shifting English pedagogy from text-focused close reading. We investigate how a move from exclusively close-reading approaches is important because of the ways in which such a scholarly practice is premised on both potentially canonical and thus Eurocentric intertexts, and the abstraction of the text from cultural and authorial sovereignty. Further, close reading limits the use of textual artefacts, and the knowledge contained within them, to literary concerns of structure, features, devices, effects, and audiences. Here we show how reader relationality involves the reader's reflective stance, the writing's contexts, the guidance of the writer, and the function of the reading process. This paper contributes to and extends approaches to English arguing that inclusion of Indigenous writing in curriculum includes but must go beyond text selection and adoption.